Pattern synthesis of conformal arrays for airborne vehicles - Morton, T.E.; Pasala, K.M. (2004 IEEE Aerospace Conference Proceedings (IEEE Cat. No.04TH8720), 2004)
This paper extends a beam pattern synthesis technique to a conformal array geometry. An array of simple slot radiating elements is postulated to cover a surface typical of the nosecone of an aircraft or missile. The far field element patterns for both polarization components are derived and applied to an iterative synthesis algorithm based on maximizing directivity subject to specified sidelobe constraints. Synthesized patterns with specified sidelobe levels are presented. Null steering is demonstrated, and beamwidth and directivity performance is considered as a function of scan angle. Near hemispheric coverage is demonstrated by assuming a capability to switch elements around the cone periphery. These results indicate the potential utility of conformal arrays for airborne applications. By continuing demonstration of useful beam patterns, directivities, and wide scan angles, conformal arrays may routinely find their way onto airborne vehicles, where they can introduce the additional benefits of reduced aerodynamic drag, weight and space savings and reduction of radome signal distortion.